High-thermal-conductivity double-sided tape and preparation method thereof

Through the combination of modified ceramic powder and carbon nanotubes, the problem of insufficient thermal conductivity of double-sided tape is solved, and high thermal conductivity and thermal stability is achieved, which is suitable for the thermal management needs of electronic equipment in the 5G era.

CN119193025APending Publication Date: 2024-12-27ANHUI MINGXUN NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411248653.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The thermal conductivity of existing double-sided tapes is insufficient, which can easily lead to problems of heat aggregation and poor bonding. Especially at high temperatures, the dispersion and viscosity of thermal conductivity of thermal fillers cannot meet the thermal management needs of electronic equipment and new energy vehicles in the 5G era.

Method used

Modified ceramic powder is used to combine metal element composite ceramics reinforced by carbon material and carbon nanotubes to prepare dense ceramic powders through sol-gel method and hot-pressing sintering technology, and form strong connections with the matrix resin to improve thermal conductivity and phase Capacity.

Benefits of technology

It achieves high thermal conductivity and good thermal stability, enhances the thermal conductivity and bonding performance of double-sided tape, and is suitable for adhesive fixation of electronic equipment in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031623070000061
    Figure BDA0005031623070000061
Patent Text Reader

Abstract

The invention provides a high-thermal-conductivity double-sided adhesive tape and a preparation method thereof. The double-sided tape comprises a base material, a glue layer and a release layer, wherein raw materials of the glue layer comprise matrix resin, a curing agent and modified ceramic powder; the modified ceramic powder is metal element multiphase ceramic reinforced by a carbon material. According to the modified ceramic powder disclosed by the invention, compact ceramic powder is obtained by utilizing a sol-gel method and a carbon thermal reaction method, and the compact ceramic powder is high in crystallinity, few in defect and excellent in heat conduction effect; and through carbon material surface modification, the compatibility with matrix resin containing a benzene ring structure can be improved while the conductive effect is further improved, so that the connection between the modified ceramic powder and the resin matrix is stronger, and the modified ceramic powder is uniformly dispersed in the matrix resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional polymers, and in particular to a high thermal conductivity double-sided adhesive tape and a preparation method thereof. Background Art

[0002] With the development of science and technology and the improvement of economic level, people have put forward higher demands on the appearance, function, personalization, intelligence, lightness, greenness and environmental protection of products. These demands have led to the gradual increase and complexity of the functions integrated on a single electronic device. In addition, the size of the device itself has gradually decreased, which has put forward higher requirements on the thermal management technology of electronic equipment, that is, the safety of the equipment.

[0003] The full name of pressure-sensitive adhesive is pressure-sensitive adhesive. Pressure-sensitive adhesive is a type of curing agent that is sensitive to pressure. During construction or use, slight pressure and a short time can quickly wet the adherend and produce a strong bonding force. Its characteristics are easy bonding, not difficult to peel off, and no adhesive will remain on the adherend after peeling to cause pollution. The adhesive layer will not dry out for a long time. It is commonly known as self-adhesive adhesive, or pressure-sensitive adhesive for short.

[0004] There are many types of pressure-sensitive adhesive products. According to different applications and needs, pressure-sensitive adhesive products include double-sided tape, single-sided tape, labels and stickers, protective films, Band-Aids, note paper adhesives, etc. Although traditional double-sided adhesive materials have good adhesive properties and are easy to use, they have been widely used in the electronics and automotive industries. However, traditional double-sided adhesive products are easy to burn and have poor thermal conductivity. They are prone to heat accumulation and cause product combustion, explosion and other dangers. Such products can basically no longer meet the needs of the electronics and electrical appliances, new energy vehicles and other industries in the 5G era.

[0005] Existing oriented double-sided tapes generally use an adhesive layer coated on a resin base or a metal film layer. Although the thermal conductivity has been improved, in the face of electronic devices that are becoming increasingly thinner and lighter and generate exponentially more heat, there are still problems such as insufficient thermal conductivity, uneven heat dissipation, and unreliable use. In addition, according to relevant statistics, various types of double-sided adhesive tapes in China have the following defects: ① The thermal conductivity coefficient is not high, the heat dissipation effect is not good, the specific surface area of ​​the micron-level thermal conductive filler is not large enough, and the adhesive tape viscosity must be guaranteed. Excessive thermal conductive fillers cannot be added. In this case, a good thermal conductive channel will not be formed. In addition, nano-level thermal conductive fillers are easy to agglomerate and unevenly dispersed, which also cannot guarantee a good thermal conductive channel; ② Adding thermal conductive fillers will greatly reduce the adhesive tape viscosity, and the viscosity will be even lower at high temperatures, and there will be a risk of debonding. To achieve a better thermal conductivity effect in the adhesive, a higher proportion of thermal conductive fillers needs to be added. The filler will dilute the proportion of the adhesive, and most of the thermal conductive fillers are polar substances, which will combine with the polar functional groups of the adhesive, and the polar functional groups that provide viscosity will fail, greatly reducing the adhesive performance. At high temperatures, the fluidity of the adhesive increases, the viscosity will be further reduced, and there will be a risk of poor adhesion.

[0006] Therefore, the current problem is that it is urgent to research and develop a double-sided tape with excellent comprehensive performance to meet the needs of the industry. Summary of the invention

[0007] Purpose of the invention: The purpose of the present invention is to provide a high thermal conductivity double-sided adhesive tape and a preparation method thereof in view of the problem that the thermal conductive adhesive currently prepared using nanoparticles as thermal conductive fillers has low thermal conductivity and poor thermal stability due to the high surface energy of the nanoparticles themselves, poor compatibility with the glue resin matrix, poor dispersibility, and easy agglomeration in the matrix.

[0008] The technical solution of the present invention:

[0009] In one aspect, the present invention provides a high thermal conductivity double-sided tape, which includes a substrate, a glue layer and a release layer. The raw materials of the glue layer include a base resin, a curing agent and a modified ceramic powder; the modified ceramic powder is a metal element composite ceramic reinforced by a carbon material.

[0010] In some embodiments, the carbon material is selected from one or more combinations of long carbon fibers, chopped carbon fibers, nanocarbon fibers, carbon nanotubes, and graphene; preferably, the carbon material is carbon nanotubes.

[0011] In some embodiments, the metal element is selected from one or more combinations of magnesium metal, lithium metal or titanium metal; preferably, the metal element is a mixed metal element of magnesium metal and titanium metal.

[0012] In some embodiments, the method for preparing the carbon material reinforced metal element composite ceramic comprises:

[0013] S1: firstly, tetraethyl orthosilicate (TEOS) is dissolved in a mixture of ethanol and deionized water, and stirred evenly, then boric acid and glucose are added to the above solution, and then silicide of metal elements is added to the solution, and stirred under heating conditions to form a mixed gel, and then the mixed gel is placed in an oven to dry, and after drying, it is calcined and naturally cooled to obtain a metal element composite ceramic;

[0014] S2: The composite ceramic powder is mixed with the carbon material by ball milling, and then sintered to obtain the carbon material reinforced metal element composite ceramic.

[0015] In some embodiments, the molar ratio of tetraethyl orthosilicate, boric acid, glucose and silicide of metal element is 1:20-30:60-100:5-20.

[0016] In some embodiments, the heating condition is 50-80° C. and the heating time is 2-5 h.

[0017] In some embodiments, the drying temperature is 100-130° C., and the drying time is 12-24 hours.

[0018] In some embodiments, the calcination temperature is 1500-1700° C., and the calcination time is 1-3 hours.

[0019] In some embodiments, based on the total mass of the modified ceramic powder as 100%, the added mass percentage of the carbon material accounts for 1-10% of the total mass of the modified ceramic powder; preferably, the added mass percentage of the carbon material accounts for 4-7% of the total mass of the modified ceramic powder.

[0020] In some embodiments, based on the total mass of the double-sided tape as 100%, the added mass percentage of the modified ceramic powder accounts for 10-30% of the total mass of the glue layer; preferably, the added mass percentage of the modified ceramic powder accounts for 10-25% of the total mass of the glue layer; the added mass percentage of the curing agent accounts for 1-5% of the total mass of the glue layer; preferably, the added mass percentage of the curing agent accounts for 2-5% of the total mass of the glue layer.

[0021] In some embodiments, the base resin is a copolymer resin of methyl methacrylate and styrene; the molecular weight of the base resin is 1000-1500.

[0022] In some embodiments, the molar ratio of methyl methacrylate to styrene is 6-9:1-4; preferably, the molar ratio of methyl methacrylate to styrene is 8:2.

[0023] In another aspect, the present invention provides a method for preparing the above-mentioned high thermal conductive double-sided adhesive tape, comprising the following steps:

[0024] Step 1: Weigh the base resin, curing agent and modified ceramic powder according to the formula, stir and mix them to obtain glue;

[0025] Step 2: Coat one side of the substrate with the glue obtained in step 1 to obtain a glue layer, and then affix a release film on the glue layer to obtain a release layer. Then, coat the other side of the substrate with the glue obtained in step 1 to obtain another glue layer, and then affix a release film on the glue layer to obtain a high thermal conductivity double-sided tape.

[0026] Beneficial effects:

[0027] 1. The modified ceramic powder of the present invention utilizes the sol-gel method and the carbon thermal reaction method. Compared with the physical mixing of ternary single-phase metal-non-metal, the modified ceramic material prepared by the present invention has the bonding between the various crystal phases that can be reflected at the nanometer level. Combined with hot pressing or SPS sintering technology, a dense ceramic powder with high crystallinity, fewer defects, and excellent thermal conductivity is obtained. After surface modification with carbon materials, the conductive effect is further improved while also improving the compatibility with the matrix resin.

[0028] 2. Through copolymerization modification of the matrix resin, a benzene ring structure is connected to the main chain of the resin. The lone electrons on the surface of the carbon nanotubes and the electrons of the large π bond on the benzene ring form a coordination bond, which makes the connection between the modified ceramic powder and the resin matrix stronger and makes the modified ceramic powder evenly dispersed in the matrix resin. DETAILED DESCRIPTION

[0029] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0030] Unless otherwise specified, the chemical reagents used in the present invention are all commercially available analytically pure.

[0031] The carbon nanotubes used in the embodiment have a diameter of 10 nm and a length of 500 nm.

[0032] The curing agent used in the embodiment is RS-3686 produced by Hongtai Ruisheng.

[0033] Preparation of modified ceramic powder 1

[0034] S1: Add 1 mol of TEOS to a mixture of ethanol and deionized water (ethanol: water volume ratio 8:2), stir evenly, then add 20 mol of boric acid and 60 mol of glucose, and then add 5 mol of metal element silicide - magnesium silicide, heat to 60°C and stir for 2 hours to obtain a mixed gel; place the mixed gel in an oven and dry it at 100°C for 12 hours. After drying, place it at 1500°C for calcination for 3 hours. After calcination, cool it naturally to obtain a metal element composite ceramic.

[0035] S2: The composite ceramic powder obtained in S1 is mixed with carbon nanotubes by ball milling in a mass ratio of 9:1, and sintered at 1800° C. to obtain a carbon material-reinforced metal element composite ceramic.

[0036] Preparation of modified ceramic powder 2

[0037] The steps for preparing modified ceramic powder 2 are the same as those for preparing modified ceramic powder 1, except that the added molar masses of TEOS, boric acid, glucose and magnesium silicide are 1 mol, 30 mol, 100 mol and 20 mol, respectively.

[0038] Preparation of modified ceramic powder 3

[0039] The steps for preparing modified ceramic powder 3 are the same as those for preparing modified ceramic powder 1, except that the added molar masses of TEOS, boric acid, glucose and magnesium silicide are 1 mol, 20 mol, 90 mol and 20 mol, respectively.

[0040] Preparation of modified ceramic powder 4

[0041] The operation steps for preparing the modified ceramic powder 4 are the same as those for preparing the modified ceramic powder 1, except that the silicide of the metal element is lithium silicide.

[0042] Preparation of modified ceramic powder 5

[0043] The steps for preparing the modified ceramic powder 5 are the same as those for preparing the modified ceramic powder 1, except that the silicide of the metal element is a mixture of titanium silicide and magnesium silicide in a mass ratio of 1:1.

[0044] Preparation of modified ceramic powder 6

[0045] The steps for preparing the modified ceramic powder 6 are the same as those for preparing the modified ceramic powder 1, except that the silicide of the metal element is a mixture of lithium silicide and magnesium silicide in a mass ratio of 1:1.

[0046] Preparation of modified ceramic powder 7

[0047] The operation steps for preparing modified ceramic powder 7 are the same as those for preparing modified ceramic powder 1, except that no carbon material is added in step S2.

[0048] Preparation of modified ceramic powder 8

[0049] The operation steps for preparing modified ceramic powder 8 are the same as those for preparing modified ceramic powder 1, except that the amount of silicide of the metal element added is 0 mol.

[0050] Preparation of modified ceramic powder 9

[0051] The steps for preparing the modified ceramic powder 9 are as follows:

[0052] The purchased TEOS, boric acid, glucose and magnesium silicide were weighed at 1 mol, 20 mol, 60 mol and 5 mol, put into a ball mill and mixed, placed in an oven at 100°C for 12 h, and calcined at 1500°C for 3 h after drying. After calcination, it was naturally cooled to obtain ceramic powder. Ceramic powder and carbon nanotubes were then added to carbon nanotubes in a mass ratio of 9:1 and ball-milled. The mixture was sintered at 1800°C to obtain modified ceramic powder 9.

[0053] Preparation of base resin

[0054] Add 50 ml of toluene to a three-necked flask, add 8 mol of methyl methacrylate and 2 mol of styrene into the three-necked flask, and stir evenly; dissolve 0.02 mol of benzoyl peroxide in 10 ml of solvent, and then slowly add the dissolved benzoyl peroxide into the three-necked flask, heat to 60°C and keep warm for 8 hours. After the reaction is completed, stop heating and cool to room temperature, pour the reactant into excess methanol to precipitate a polymer, filter and separate the polymer, wash and dry to obtain a base resin.

[0055] The matrix resin was scanned using a Nicolet FTIR 6700 infrared spectrometer produced by Nicolet Co., Ltd., USA, at 1730 cm -1 C=O stretching vibration appears at 1100cm -1 COC stretching vibration appears at 1600cm -1 The C=C stretching vibration of the benzene ring appears at 3000cm -1 The CH stretching vibration appears at , indicating that the matrix resin is successfully synthesized.

[0056] Examples 1-6

[0057] Step 1: Weigh the base resin, curing agent and modified ceramic powder prepared above in a mass ratio of 70:25:5, stir and mix to obtain glue;

[0058] Step 2: Apply the glue obtained in step 1 on one side of the PET substrate to obtain a glue layer, and then laminate a PET release film on the glue layer to obtain a release layer. Then, apply the glue obtained in step 1 on the other side of the substrate to obtain another glue layer, and laminate a PET release film on the glue layer to obtain a high thermal conductivity double-sided tape.

[0059] The types of modified ceramic powders used in the examples are shown in Table 1.

[0060] Table 1 Correspondence between the examples and the modified ceramic powder in the raw materials

[0061] Example Modified ceramic powder types Example 1 Modified ceramic powder 1 Example 2 Modified ceramic powder 2 Example 3 Modified ceramic powder 3 Example 4 Modified ceramic powder 4 Example 5 Modified ceramic powder 5 Example 6 Modified ceramic powder 6

[0062] Comparative Example 1

[0063] The preparation method of Comparative Example 1 is the same as that of Example 1, except that the type of modified ceramic powder is modified ceramic powder 7.

[0064] Comparative Example 2

[0065] The preparation method of Comparative Example 2 is the same as that of Example 1, except that the type of modified ceramic powder is modified ceramic powder 8.

[0066] Comparative Example 3

[0067] The preparation method of Comparative Example 4 is the same as that of Example 1, except that the type of modified ceramic powder is modified ceramic powder 9.

[0068] Comparative Example 4

[0069] The preparation method of Comparative Example 3 is the same as that of Example 1, except that polymethyl methacrylate with the same molecular weight is used instead of the base resin.

[0070] The double-sided adhesive tapes obtained from the above examples and comparative examples were subjected to the following tests:

[0071] 1. Peel strength test: According to GBT-2792-2014 standard, the test is carried out using a universal tensile machine.

[0072] 2. Thermal conductivity test: According to ASTM D5470 standard, use thermal conductivity tester to test.

[0073] 3. Weather resistance: Peel off the release layer of the double-sided tape, stick it on a glass substrate, place it in an environment of 110°C for 12 hours, and observe whether the double-sided tape is deformed, fallen off or cracked.

[0074] The test results are shown in Table 2.

[0075] Table 2 Test results of tests 1-3

[0076]

[0077] It can be seen from the above table that the double-sided tapes prepared in Examples 1-6 have good peel strength and viscosity, and high thermal conductivity, and are suitable for bonding and fixing components in heat-generating components such as mobile phone batteries and CPUs.

[0078] It can be seen from the combination of Comparative Examples 1 and 4 that in the process of preparing modified ceramic powder, the grafted carbon material is not only beneficial to improving the thermal conductivity of the modified ceramic powder, but also beneficial to improving the connection strength between the carbon material and the benzene-containing resin. The lone electrons on the surface of the carbon nanotubes and the electrons of the large π bonds on the benzene ring form coordination bonds, which makes the connection between the modified ceramic powder and the resin matrix stronger, makes the modified ceramic powder evenly dispersed in the matrix resin, and enhances weather resistance and stability.

[0079] It can be seen from Examples 1-6 that the addition of silicides of different metal elements will have some effect on the thermal conductivity of the modified ceramic powder, and the modified ceramic powder prepared with titanium and magnesium mixed silicide has better peel strength and thermal conductivity, indicating that the use of titanium and magnesium mixed silicide for preparation is more conducive to improving the performance of the modified ceramic powder.

[0080] The present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.

Claims

1. A high thermal conductivity double-sided tape, comprising a substrate, a glue layer and a release layer, characterized in that: The raw materials of the glue layer include base resin, curing agent and modified ceramic powder; the modified ceramic powder is a metal element composite ceramic reinforced by carbon material.

2. The high thermal conductivity double-sided tape according to claim 1, characterized in that: The carbon material is selected from one or more combinations of long carbon fibers, short chopped carbon fibers, nano carbon fibers, carbon nanotubes, and graphene.

3. The high thermal conductivity double-sided tape according to claim 1, characterized in that: The metal element is selected from one or more combinations of magnesium metal, lithium metal or titanium metal.

4. The high thermal conductivity double-sided tape according to claim 1, characterized in that: The preparation method of the carbon material reinforced metal element composite ceramic comprises: S1: First, dissolve ethyl orthosilicate in a mixture of ethanol and deionized water, stir evenly, then add boric acid and glucose to the solution, then add the silicide of the metal element to the solution, stir under heating conditions to form a mixed gel, then put the mixed gel into an oven to dry, calcine after drying, and cool naturally to obtain a metal element composite ceramic; S2: The composite ceramic powder is mixed with the carbon material by ball milling, and then sintered to obtain the carbon material reinforced metal element composite ceramic.

5. The high thermal conductivity double-sided adhesive tape according to claim 4, characterized in that: The molar ratio of tetraethyl orthosilicate, boric acid, glucose and silicide of metal elements is 1:20-30:60-100:5-20.

6. The high thermal conductivity double-sided tape according to claim 4, characterized in that: The heating condition is 50-80°C and the heating time is 2-5h; the drying temperature is 100-130°C and the drying time is 12-24h; the calcination temperature is 1500-1700°C and the calcination time is 1-3h.

7. The high thermal conductivity double-sided tape according to claim 4, characterized in that: Taking the total mass of the modified ceramic powder as 100%, the added mass percentage of the carbon material accounts for 1-10% of the total mass of the modified ceramic powder.

8. The high thermal conductivity double-sided adhesive tape according to claim 1, characterized in that: Taking the total mass of the glue layer as 100%, the added mass percentage of the modified ceramic powder accounts for 10-30% of the total mass of the glue layer; the added mass percentage of the curing agent accounts for 1-5% of the total mass of the glue layer, and the remainder is the matrix resin.

9. The high thermal conductive double-sided tape according to claim 1, characterized in that: The base resin is a copolymer resin of methyl methacrylate and styrene.

10. The method for preparing the high thermal conductive double-sided adhesive tape according to any one of claims 1 to 9, characterized in that: The steps include: Step 1: Weigh the base resin, curing agent and modified ceramic powder according to the formula, stir and mix them to obtain glue; Step 2: Coat one side of the substrate with the glue obtained in step 1 to obtain a glue layer, and then affix a release film on the glue layer to obtain a release layer; then coat the other side of the substrate with the glue obtained in step 1 to obtain another glue layer, and then affix a release film on the glue layer to obtain a high thermal conductivity double-sided tape.